Indonesian Government Bureaucracy In The Perspective Of Reinventing Government: “How The Entrepreneurial Spirit Is Transforming The Public Sector” - Haeruddin; Toding, Sukanto; Nashar , Abdul (Arus Jurnal Sosial dan Humaniora, 2025)
The mandate of the Government of the Republic of Indonesia is to be more independent and improve its performance in managing its potential, as well as increasing public participation in the implementation of regional government policies, both at the provincial and district/city levels in Indonesia. The concept of "Reinventing Government" is a bureaucratic concept that can foster an entrepreneurial spirit within government officials and further improve their performance, as an effort to achieve the goals of governance in Indonesia. The concept of "Reinventing Government" can be a solution to the problems of government bureaucracy in Indonesia if its implementation is appropriate to the economic, social, political, and cultural conditions and receives support from the government, business, and the community.